The Functional Role of the Periphery in Emotional Language Comprehension - Havas, David A.; Matheson, James (Frontiers in Psychology, 2013)
Language can impact emotion, even when it makes no reference to emotion states. For example, reading sentences with positive meanings (“The water park is refreshing on the hot summer day”) induces patterns of facial feedback congruent with the sentence emotionality (smiling), whereas sentences with negative meanings induce a frown. Moreover, blocking facial afference with botox selectively slows comprehension of emotional sentences. Therefore, theories of cognition should account for emotion-language interactions above the level of explicit emotion words, and the role of peripheral feedback in comprehension. For this special issue exploring frontiers in the role of the body and environment in cognition, we propose a theory in which facial feedback provides a context-sensitive constraint on the simulation of actions described in language. Paralleling the role of emotions in real-world behavior, our account proposes that (1) facial expressions accompany sudden shifts in wellbeing as described in language; (2) facial expressions modulate emotional action systems during reading; and (3) emotional action systems prepare the reader for an effective simulation of the ensuing language content. To inform the theory and guide future research, we outline a framework based on internal models for motor control. To support the theory, we assemble evidence from diverse areas of research. Taking a functional view of emotion, we tie the theory to behavioral and neural evidence for a role of facial feedback in cognition. Our theoretical framework provides a detailed account that can guide future research on the role of emotional feedback in language processing, and on interactions of language and emotion. It also highlights the bodily periphery as relevant to theories of embodied cognition.